Drug-related Atrioventricular Block: Is It a Benign Condition? - Sayah, Sima; Akbarzadeh, Mohammad Ali; Emkanjoo, Zahra; Mollazadeh, Reza; Shahrzad, Shahab; Bahrololoumi Bafruee, Negar (International Journal of Cardiovascular Practice, 2016)
Introduction: Prognosis of the patients with beta blocker or calcium channel blocker induced AV block is not well known to date.Methods: All patients with symptomatic second-degree or third-degree atrioventricular block (AV) referred to our institution during one year were recuited prospectively and classified in two groups based on drug consumption (beta blocker/calcium channel blocker versus none). They were followed for six months and then collected data was analyzed.Results: The study included 49 patients, 28 patients (age 60.1 Â± 20, 19 male) did not use any beta blocker or calcium channel blocker (No- DU group) and other 21 patients (age 73.5 Â± 10.4, 7 male) receivd beta blocker, calcium channel blocker or both at the time of AV block (DU group). No-DU group was significantly younger than DU group. The most common atrial rhythm in both groups was sinus. There was no significant difference in QRS wideness or ventricular rate. AV block regressed in 43% of the DU group after discontinuation of drug for five half-life, but, Mobitz type 2 or complete AV block occurred again during six months in 50% of them without Â consumption of the culprit drug.Conclusions: More than two third of the patients who developed AV block on beta blocker and/or calcium channel blocker needed permanent pacemaker in six months of follow- up, so we concluded that the development of AV block was not as benign as it seems in these patients.